2008
DOI: 10.1007/s10856-008-3455-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surface mineral and osteopontin on the formation and function of murine bone marrow-derived osteoclasts

Abstract: The phosphorylated glycoprotein osteopontin (OPN) is involved in the regulation of biomineralization under normal and pathological conditions. Its actions include inhibiting apatite crystal growth and promoting the formation and function of mineral resorbing cells, including osteoclasts (OCL). The purpose of this study was to develop stable apatitic mineral surfaces and determine their influence on OCL formation and mineral resorption from bone marrow macrophages derived from OPN wild-type (OPN +/+) and OPN de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…These findings stress earlier studies on the impact of mineral substrates on osteoclastogenesis, which showed increased osteoclast formation of osteopontin-deficient cells when culture was performed on plastic that was no longer present when culture was performed on bone (40). However, F-actin staining demonstrated that S100A8-stimulated osteoclasts contained significantly more actin rings per cell.…”
Section: Discussionsupporting
confidence: 85%
“…These findings stress earlier studies on the impact of mineral substrates on osteoclastogenesis, which showed increased osteoclast formation of osteopontin-deficient cells when culture was performed on plastic that was no longer present when culture was performed on bone (40). However, F-actin staining demonstrated that S100A8-stimulated osteoclasts contained significantly more actin rings per cell.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, Rajachar et al [2008] showed that OPN À / À bone marrow-derived macrophages formed more osteoclasts on TCP than OPN þ / þ macrophages, a finding consistent with previous in vitro and in vivo investigations of OPN null mice [Rittling et al, 1998;Chellaiah et al, 2003b]. Although we found no difference in osteoclast number on OPN compared to HA, all resorption parameters were elevated except for sealing zone formation.…”
Section: Il-1b Was Measured By Elisa At 24 and 48 H (Bd) Each Data supporting
confidence: 91%
“…Although we found no difference in osteoclast number on OPN compared to HA, all resorption parameters were elevated except for sealing zone formation. This increased resorptive capacity in the presence of OPN, with the exception of one study [Contractor et al, 2005], matches the rest of the literature demonstrating that OPN is required for proper bone resorption both in vivo and in vitro [Razzouk et al, 2002;Chellaiah et al, 2003b;Rajachar et al, 2008]. Taken together, these results highlight the important contribution of matrix proteins in modulating bone remodeling.…”
Section: Il-1b Was Measured By Elisa At 24 and 48 H (Bd) Each Data supporting
confidence: 76%
See 1 more Smart Citation
“…OPN works as an anchor to promote attachment of osteoclasts to bone for bone resorption. Osteoclasts deficient in OPN are hypomotile and exhibit decreased capacity for bone resorption, and bones lacking OPN are less readily remodeled [35][36][37]. The differentiation of cells of the monocytic lineage into mature osteoclasts is specifically induced by the tumor necrosis factor-related factor and receptor activator of NF-κB ligand (RANKL) [38].…”
Section: Discussionmentioning
confidence: 99%